2014
DOI: 10.1002/ange.201405362
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Stoichiometry of Pyrococcus furiosus RNase P, a Multi‐Subunit Catalytic Ribonucleoprotein Complex, by Surface‐Induced Dissociation and Ion Mobility Mass Spectrometry

Abstract: We demonstrate that surface‐induced dissociation (SID) coupled with ion mobility mass spectrometry (IM‐MS) is a powerful tool for determining the stoichiometry of a multi‐subunit ribonucleoprotein (RNP) complex assembled in a solution containing Mg2+. We investigated Pyrococcus furiosus (Pfu) RNase P, an archaeal RNP that catalyzes tRNA 5′ maturation. Previous step‐wise, Mg2+‐dependent reconstitutions of Pfu RNase P with its catalytic RNA subunit and two interacting protein cofactor pairs (RPP21⋅RPP29 and POP5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 59 publications
0
10
2
Order By: Relevance
“…Native electrospray ionization/ion mobility-mass spectrometry (ESI/IM-MS) is emerging as a powerful technique for capturing key structural features of proteins and their complexes. [1][2][3][4][5][6][7] Next to the mass-to-charge ratio (m/z), it provides the charge state distributions (CSD) and collision cross sections (CCS) for all species present in the gas phase. From these, one can extract their stoichiometry, topology, connectivity, dynamics and shape, as well as distribution of copopulated assembly and folding states.…”
Section: Toc Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Native electrospray ionization/ion mobility-mass spectrometry (ESI/IM-MS) is emerging as a powerful technique for capturing key structural features of proteins and their complexes. [1][2][3][4][5][6][7] Next to the mass-to-charge ratio (m/z), it provides the charge state distributions (CSD) and collision cross sections (CCS) for all species present in the gas phase. From these, one can extract their stoichiometry, topology, connectivity, dynamics and shape, as well as distribution of copopulated assembly and folding states.…”
Section: Toc Main Textmentioning
confidence: 99%
“…Our multi-scale approach is applied to a peptide fragment containing the 16 N-terminal residues of the ~40 amino acid-long amyloid- peptide (A(1-16)), a promising therapeutic target to reduce cognitive deficits for Alzheimer's disease patients, 31 which is broadly studied by MS characterization in aspects of structure 32 as well as their aggregation behaviors. [33][34] The maximum charge state (highest charge) of A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) is here predicted to be 4+ by our established hybrid Monte Carlo (MC)/MD-based protocol [22][23] (see Figure S1 in Supporting Information for details). Accordingly, the mass spectrum of the peptide shows a maximum charge state detectable at 4+ and a narrow CSD dominated by 3+ (main charge state, see Figure S2 in Supporting Information).…”
Section: Toc Main Textmentioning
confidence: 99%
“…An emerging alternative that can complement these techniques, especially when RNA-protein complexes show unfavorable conformational dynamics that complicate NMR data interpretation 2 , 3 or fail to crystallize properly 4 , 5 , is native top-down mass spectrometry (MS) 6 . We have recently demonstrated that native electrospray ionization (ESI) 7 12 provides time-resolved, stoichiometric information on complexes of transactivation responsive (TAR) RNA and trans-activating (tat) peptide from human immunodeficiency virus type 1 (HIV-1), and that collisionally activated dissociation (CAD) can reveal tat binding sites of TAR RNA at the single-nucleotide level 6 . This native top-down MS approach relies on the preservation of electrostatic interactions between protonated peptides and deprotonated RNA at energies that are sufficiently high for phosphodiester backbone bond cleavage 6 , for which as few as two arginine residues are sufficient 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study nano‐electrospray ionization mass spectrometry (nano‐ESI MS) was used to determine the AmrZ oligomeric state in solution. Mass spectrometry precisely measures the size of a molecule and nano‐ESI MS allows the detection of proteins or protein complexes when they are still folded (Karas et al ., ; Ma et al ., ). As shown in Fig.…”
Section: Resultsmentioning
confidence: 97%